Qualitative emphysema and risk of COPD hospitalization in a multicenter CT lung cancer screening cohort study. (January 2021) - Gazourian, Lee; Thedinger, William B.; Regis, Shawn M.; Pagura, Elizabeth J.; Price, Lori Lyn; Gawlik, Melissa; Stefanescu, Cristina F.; Lamb, Carla; Rieger-Christ, Kimberly M.; Singh, Harpreet; Casasola, Marcel; Walker, Alexander R.; et al.
Abstract: Background: In the United States, 9 to 10 million Americans are estimated to be eligible for computed tomographic lung cancer screening (CTLS). Those meeting criteria for CTLS are at high-risk for numerous cardio-pulmonary co-morbidities. The objective of this study was to determine the association between qualitative emphysema identified on screening CTs and risk for hospital admission. Study design and Methods: We conducted a retrospective multicenter study from two CTLS cohorts: Lahey Hospital and Medical Center (LHMC) CTLS program, Burlington, MA and Mount Auburn Hospital (MAH) CTLS program, Cambridge, MA. CTLS exams were qualitatively scored by radiologists at time of screening for presence of emphysema. Multivariable Cox regression models were used to evaluate the association between CT qualitative emphysema and all-cause, COPD-related, and pneumonia-related hospital admission. Results: We included 4673 participants from the LHMC cohort and 915 from the MAH cohort. 57% and 51.9% of the LHMC and MAH cohorts had presence of CT emphysema, respectively. In the LHMC cohort, the presence of emphysema was associated with all-cause hospital admission (HR 1.15, CI 1.07–1.23; p < 0.001) and COPD-related admission (HR 1.64; 95% CI 1.14–2.36; p = 0.007), but not with pneumonia-related admission (HR 1.52; 95% CI 1.27–1.83; p < 0.001). In the MAH cohort, the presence of emphysema was only associated with COPD-related admission (HR 2.05; 95% CI 1.07–3.95; p = 0.031). Conclusion: Qualitative CT assessment of emphysema is associated with COPD-related hospital admission in a CTLS population. Identification of emphysema on CLTS exams may provide an opportunity for prevention and early intervention to reduce admission risk. Highlights: Qualitative emphysema is associated with risk for COPD hospitalization. Lung cancer screening represents are an opportunity to screen for COPD. Lung cancer screening represents an opportunity to improve vaccination rates. Lung cancer screening represents an opportunity to improve smoking cessation rates.